Modeling microwave drying kinetics and moisture diffusivity of Mabonde banana variety - Omolola, Adewale O.; Jideani, Afam I. O.; Kapila, Patrick F. (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: This study investigates the microwave drying kinetics of thin layer Mabonde banana variety (MBV) at power levels between 100 and 300 W. Six mathematical drying models: Wang and Singh, Verma, Two-term, Page, Two term exponential, and Logarithmic models were fitted to experimental drying data obtained from the study. The statistical consistency of the models was determined using statistical parameters including coefficient of determination, mean bias error, root mean square error, and reduced Chi square. Moisture migration from banana slices was described using the Fick’s diffusion model. The effective diffusivity was calculated. The results indicated that drying took place largely in the falling rate period. The time required to reduce the moisture of banana to a certain level was dependent on the microwave output, being the longest at 100 W and shortest at 300 W. The effective moisture diffusivity increased with increasing microwave power with values at 4.89×10-10, 1.09×10-9 and 1.69×10-9 m2/s at 100, 200, and 300 W, respectively. The Wang and Singh model gave the best results for the description of thin layer drying of MBV.Keywords: Mabonde banana variety, microwave, drying models, drying kinetics, effective moisture diffusivityDOI: 10.3965/j.ijabe.20140706.013Citation: Omolola A O, Jideani A I O, Kapila P F. Modeling microwave drying kinetics and moisture diffusivity of Mabonde banana variety. Int J Agric & Biol Eng, 2014; 7(6): 107－113.